PERANCANGAN APLIKASI PEMBELAJARAN PENGENALAN KOSAKATA PADA ANAK TUNARUNGU SISWA SDLB KEFAMENANU - Risald; Yokmiawanti Selan; Darsono Nababan; Budiman Baso (Jurnal Komputer dan Teknologi, 2025)
Deafness is a condition in which a person experiences significant hearing loss. This loss of hearing ability makes it difficult for individuals to communicate and adapt to their surroundings, especially when it affects students. One of the main challenges faced by deaf students is communication during the learning process. The Vocabulary Learning Introduction Application is an Android-based application designed to assist hearing-impaired users during teaching and learning activities. With this application, users simply need to select and tap the available features, which will then direct them to the appropriate learning pages. This application is highly beneficial for deaf students, as it helps facilitate communication during the learning process and also trains students to better understand and memorize vocabulary using sign language. Based on the designed learning scenarios, the results show that students are trained to understand and retain vocabulary more easily in their memory. Given their limitations, students are not pressured to perform but are instead guided according to their individual abilities to understand vocabulary.